PHYSICAL SELF-CONCEPT, ANTHROPOMETRY AND BODY COMPOSITION IN PREADOLESCENTS - Stojan Puhalj; Črtomir Matejek; Jurij Planinšec (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2013)
The main aim of this study was to determine the relationship of morphologic features and body composition to physical self-concepts in boys and girls separately. This research included 630 children from north-eastern Slovenia, aged 9 to 11 years (M = 10.01; SD = .810), of which 311 were boys and 319 were girls. Morphologic features of the children were measured with the use of a standardized anthropometric instrumentation; the Maltron BF-907 Body Composition Analyzer was used for the measurement of body fat, fat-free mass, and body water proportions. The gender, age, and physical self-concept data were acquired through the French version of The Physical Self-Inventory - a short form questionnaire for determining the physical self-concept of adolescents, adapted to Slovenia. The relation between individual morphological features and physical self-concept was determined by regression analysis. Statistical significance was established at 0.05. The results show that the physical self-concept is more closely connected with body composition and morphologic features in boys than in girls, whereas the body fat proportion is the strongest predictor of physical self-concept in boys. The findings show that, particularly in boys, the physical self-concept is also largely based on the morphologic features and body composition. It is necessary to give special attention to boys, as we often think that boys are not as concerned with the physical appearance as girls.